2017
DOI: 10.1002/em.22100
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variants in the promoter region of a novel antisense long noncoding RNA RP11‐392P7.6 and colorectal cancer risk

Abstract: There is a widespread occurrence of antisense transcripts' regulation on cancer-related genes in cancer biology. RP11-392P7.6 is antisense to the coding region of cancer-related gene GPRC5D, which has been found recently. The aim of this study was to investigate the associations of tagSNPs in the promoter region of RP11-392P7.6 with the risk of colorectal cancer. We conducted a two-stage case-control study, with a discovery set (320 cases and 319 controls) and a validation set (501 cases and 538 controls). Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Participants with colorectal polyps (hyperplastic polyp or adenoma) were drawn from a population-based cohort since 1989 in Jiashan County, Zhejiang Province, China. It has been described in detail previously [22, 23]. For each participant, a histologically confirmed colorectal lesion (hyperplastic polyp, adenoma, or carcinoma) and a distant normal mucosa sample were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Participants with colorectal polyps (hyperplastic polyp or adenoma) were drawn from a population-based cohort since 1989 in Jiashan County, Zhejiang Province, China. It has been described in detail previously [22, 23]. For each participant, a histologically confirmed colorectal lesion (hyperplastic polyp, adenoma, or carcinoma) and a distant normal mucosa sample were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The third study focused on the promoter region of lncRNA RP11-392P7.6 which is an antisense to the G-protein coupled receptor family C group 5-member D (CPRC5D) a coding region of the cancer-related gene. The SNP rs10845671 on lncRNA RP11-392P7.6 is associated with an increased risk of CRC, indicating that it may contribute to the CRC susceptibility and may be a candidate biomarker for CRC risk prediction [49]. LncRNA colorectal cancer associated transcript 1 (CCAT1) is a relatively novel lncRNA, whose over-expression is demonstrated in early stage of tumorigenesis and in later disease phases of CRC.…”
Section: Methods For Detection Of Snps and Measurement Of Associatmentioning
confidence: 99%
“…lncRNA RP11‐362K14.5 SNP rs1317082 T > C reduced the expression of CCSlnc362 by creating a bind site for miR‐4658, thus decreased the risk of CRC 38 . A novel SNP rs10845671, locating in lncRNA RP11‐392P7.6 promoter region, was associated with the susceptibility of CRC 39 . Our previous study has shown that MALAT1 rs664589 G allele upregulated MALAT1 expression by binding miR‐194‐5p and promoted CRC development 40 .…”
Section: Discussionmentioning
confidence: 94%